Evolution of Physicochemical Properties, Phenolic Acid Accumulation, and Dough-Making Quality of Whole Wheat Flour During Germination Under UV-B Radiation - Tian, Chao; Wang, Yue; Yang, Tianbao; Sun, Qingjie; Ma, Meng; Li, Man (Frontiers in Nutrition, 2022)
The effects of ultraviolet-B (UV-B) radiation on the physiological properties, phenolic acid accumulation, and dough-making quality of wheat during germination were investigated. UV-B radiation inhibited the wheat sprout length and reduced the dry matter loss. As phenolic acids were principally present in the kernels' bran, UV-B radiation could promote their accumulation in the interior of germinated wheat (GW). The total phenolic compounds, ascorbic acid, and antioxidant activity were also enhanced significantly during germination with UV-B. UV-B improved the development time, stability time, rheological properties, and viscosity of GW, and inhibited the α-amylase activity, the destruction of the amorphous region of starch particles, and the proteins degradation process during germination, and thus the deterioration of dough-making quality caused by germination was inhibited. Therefore, UV-B radiation could be a potential approach to enhance the nutritional and dough-making quality of germinated whole wheat flour.